Gestión Administrativa de la Comisión Vocacional de la Diócesis De Babahoyo - Villamar Carpio, Víctor Joel (2017)
he current diocese of Babahoyo is usually administered by a principal member who is the bishop and three secondary members who are the vicars, these are delegates to the three areas with which the diocese has such as the north, south and center , it is necessary to emphasize that at the present time the administration by assuming a Priest who exercises the position of Diocesan Administrator, but not of Bishop, the Diocese as such has a total of 33 ecclesiastical parishes, that is to say, main churches in the different cantons and civil parishes of the province, these principal parishes are in charge of priests of the same diocese as well as missionary priests of friendly dioceses, they are in charge of the attention of all the chapels that are around their ecclesiastical parishes.